ANALISIS PENGARUH HARGA, LAYANAN CASH ON DELIVERY (COD) DAN KEPUASAN PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Pelanggan Platfrom Shopee di Semarang) - Naim Al Asror, Muhammad Ainun; Wahyuningsih, Susanti (STIE PENA, 2024)
The purpose of this research is to determine the influence of price on purchasing decisions, and to determine the influence of cash on delivery (COD) services on purchasing decisions, as well as to determine the influence of customer satisfaction on purchasing decisions. The research method used in this research is multiple linear regression. The population of this study were direct visitors to the Manunggal Jati Semarang swimming pool. The sample in this study amounted to 96 people using the Purposive Sampling technique, namely a sampling technique with certain considerations, the sample determined had predetermined criteria, namely people who had made purchases on the Shopee Platform. The data collection method in this research is by distributing questionnaires via Google Form. The analytical tool used is multiple linear regression using SPSS. The type of data used is primary data. Based on the results of the research, partially there is a positive and significant influence between Price influencing Purchasing Decisions, the t value obtained is 4.595 > t table 1.661 or significant 0.000 < 0.05, partially Cash On Delivery (COD) services influence the Purchasing Decisions obtained by the t value calculated 2.564 > t table 1.661 or significant 0.012 > 0.05, and partially Customer Satisfaction has an influence on Purchasing Decisions obtained by a t value of 2.573 > t table 1,661 or significant 0.012 < 0.05. Simultaneously Price, partial Cash On Delivery (COD) Service, and Customer Satisfaction partially influence Purchasing Decisions, the F count of 49.666 is greater than the F table of 2.699 or significant 0.000 < 0.05. Keywords: Price, Cash On Delivery (COD) Service, Customer Satisfaction, and Purchasing Decisions.